2016
DOI: 10.1080/02699206.2016.1219920
|View full text |Cite
|
Sign up to set email alerts
|

Production of mental state terms in narratives of Mandarin-speaking children with autism spectrum disorder

Abstract: This study investigates the ability of Mandarin-speaking children with autism spectrum disorder (ASD) to use mental state terms in narratives. The narrative data are from 16 children with ASD and 16 typically developing children, matched on language and cognitive abilities. The narratives were elicited using Frog, where are you? Participants' use of lexical expressions referring to emotion, cognition, desire and perception was examined. The 'deer episode' of the story was chosen to analyse children's ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Although several studies on narratives of Mandarin-speaking children with ASD have reported that they failed to provide enough information to meet listeners’ needs, these studies were mainly concerned with the structural or evaluative aspect of narratives (e.g., Chen & Chang, 2005; Sah & Torng, 2015, 2016; Tsou & Cheung, 2007). The referential abilities of Mandarin-speaking autistic children are relatively much less understood.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies on narratives of Mandarin-speaking children with ASD have reported that they failed to provide enough information to meet listeners’ needs, these studies were mainly concerned with the structural or evaluative aspect of narratives (e.g., Chen & Chang, 2005; Sah & Torng, 2015, 2016; Tsou & Cheung, 2007). The referential abilities of Mandarin-speaking autistic children are relatively much less understood.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“… 3. As part of another study (Sah & Torng, 2016) involving this sample, more detailed data about participants’ characteristics were reported in that paper. …”
mentioning
confidence: 99%
“…Children’s acquisition of narrative discourse has been investigated in diverse populations and languages including Arabic (Hipfner- et al, 2015; Fichman et al, 2017; Sah & Torng, 2019), and this research has outlined some general patterns in the acquisition of narrative skills across languages (Lucero, 2015). Yet, few studies have focused on narrative skills in Arabic diglossia (however, see Leikin et al, 2014; Ravid et al, 2014), a context characterized by the co-existence of two linguistically distant language varieties: a spoken variety used for everyday speech and in which narrative skills probably first develop, and a standard variety which is acquired later and in which narratives that are read from print are expected to be delivered.…”
Section: Introductionmentioning
confidence: 99%
“…Varios estudios utilizan la narración a partir de imágenes en poblaciones incluidas dentro del espectro autista (Siller, Swanson & Teachworth, 2014;Sah & Torng, 2017). Rumpf, Kamp-Becker, Becker y Kauschke (2012) estudiaron lenguaje sobre estados internos y narraciones a partir de un libro de imágenes llamado "Tuesday" de Wiesner (1991).…”
Section: Cognición Social Y Evaluación Del Lenguaje: El Trastorno Del...unclassified